ALIGNMENT OF MALAYSIA AND ASEAN AGREEMENTS ON ICT LAWS: A REVIEW - Manap, Nazura Abdul (Faculty of Law, Universitas Brawijaya, 2015)
The mega Multimedia Super Corridor (MSC) project launched in 1996 is a strong endorsement of the Malaysian governmentâ€™s commitment towards developing the ICT industry in Malaysia. To attract world-class technology companies and prepare the local ICT industry, the government has offered MSC Malaysia Status to companies developing or using multimedia technologies in producing and enhancing their products and services and locating in any of the 26 Cybercities and Cyber centres in Malaysia. MSC status confers incentives, rights and privileges under the MSC Malaysia Bill of Guarantees. This ICT initiative also underlies Malaysiaâ€™s commitment to lead the region in protecting intellectual property and adherence to cyber laws. As a member of E-ASEAN this assurance aligns with the e-ASEAN initiative â€œâ€¦to adopt electronic commerce regulatory and legislative frameworks that create trust and confidence for consumers and facilitate the transformation of businesses towards the development of e-ASEANâ€. This paper identifies and analyses the extent of the Malaysian governmentâ€™s compliance with e-ASEAN principles particularly in the legal and regulatory aspects.